Pemanfaatan Limbah Kain Perca Dalam Permeberdayaan Ekonomi Islam Kreatif di Desa Ploso, Kec. Jumapolo - Yetty Faridatul Ulfah; Izzun Khoirun Nissa; Ahmad Fathir Qodri; Khadijah; Muthiah Zahrotul (Scimadly Publishing, 2023)
Patchwork waste is very difficult inorganic to be decomposed by the environment. In this case, it becomes a problem if it is just accumulated and then burnt which results in environmental pollution because it creates smoke and gases which are not good for health. Thus, as movers from academia, we conduct training, namely the utilization of patchwork waste into creative products having high selling value. We held this community service activity with PKK wives in Ploso Village and fellow PKN IIM Surakarta students who participated in the implementation. The implementation method in this service started from initial observations regarding the situation, offering solutions and outreaching programs and directing the training. This service activity aims to raise awareness and concern for PKK wives regarding the existence of inorganic waste around the environment, especially patchwork and also to provide knowledge related to selling power so that it can increase income both in PKK and family cash.